Awareness and Access of Research Output from Faculty of Agriculture, Nnamdi Azikiwe University to Farmers in Awka Metropolis (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The study examined awareness and access of research output from Faculty of Agriculture, Nnamdi Azikiwe University (FANAU) to farmers in Awka Metropolis, Anambra State, Nigeria. Multiple stage sampling technique was used to select 100 respondents from residents within and around Awka Metropolis. Primary data were collected using interview schedule and focus group discussion. Data collected were analysed using descriptive statistics. The Hypothesis was tested using independent T Test to determine significant differences in the socio-economic characteristics of respondents and their access to research output from FANAU. Results revealed that only 35% of the farmers interviewed were aware of FANAU research output. Out of the 35 farmers that were aware, 66.0% became aware through radio. Only 28% of farmers reported that they have access to research output from FANAU. About 91%of the farmers that were aware of the research output from FANAU, was in the area of crop production. More than 95% of the farmers that had access, expressed difficulty in accessing FANAU research output. Lack of link ( = 3.42) between farmers and researchers was perceived by farmers as the most serious challenge in accessing research output from FANAU. The study established that socio-economic characteristics such as age (p
Keywords: Access; Awareness; Awka Metropolis; Farmers; Research output